(untitled) (International relations and international law Journal, 2016)
This article is devoted to the questions of convergence of national legal systems. The opinions of the authors on the definition and forms of convergence of national legal systems are different. In the article there was paid more attention on the definition of terms of convergence of national legal systems, harmonization and unification of legislation. According to the opinions of the various authors in spite of the lack of common solutions, we can see that the definitions of these terms are identical and similar. In this article there are investigated the questions of convergence, harmonization and unification of national legal systems, legislations of the countries.